Nontraumatic chylothorax: Revisited - Banerjee Debasish (Wolters Kluwer Medknow Publications, 2007)
A 2-month-old girl came with breathlessness of 5 days′ duration. Clinical examination and plain chest radiograph showed it to be pleural effusion. On sonographically guided aspiration, the effusion fluid was found to be chyle. Introduction of intercostal thoracic drainage tube and antibiotics helped the baby to recover. It is mainly the role of nutritional support in the form of using medium-chain-triglyceride-containing feed, which is discussed in details in the case report. There was no need of any surgery.